Soybean Inoculated With One Bradyrhizobium Strain Isolated at Elevated [CO2] Show an Impaired C and N Metabolism When Grown at Ambient [CO2] - Soba, David; Aranjuelo, Iker; Gakière, Bertrand; Gilard, Françoise; Pérez-López, Usue; Mena-Petite, Amaia; Muñoz-Rueda, Alberto; Lacuesta, Maite; Sanz-Saez, Alvaro (Frontiers in Plant Science, 2021)
Soybean (Glycine max L.) future response to elevated [CO2] has been shown to differ when inoculated with B. japonicum strains isolated at ambient or elevated [CO2]. Plants, inoculated with three Bradyrhizobium strains isolated at different [CO2], were grown in chambers at current and elevated [CO2] (400 vs 700 ppm). Together with nodule and leaf metabolomics profile, characterization of nodule N-fixation and exchange between organs was tested through 15N2-labelling analysis. Soybeans inoculated with SFJ14-36 strain (isolated at elevated [CO2]) showed a strong metabolic imbalance, at nodule and leaf levels when were grown at ambient [CO2], probably due to an insufficient supply of N by nodules, as showed by 15N2-labelling. In nodules, due to photoassimilate’s shortage, C may be diverted to aspartate instead of malate in order to improve the efficiency of the C source sustaining N2-fixation. In leaves, photorespiration and respiration were boosted at ambient [CO2] in plants inoculated with this strain. Additionally, free phytol, antioxidants and fatty acids content could be indicating induced senescence due to oxidative stress and lack of nitrogen. Therefore, plants inoculated with Bradyrhizobium strain isolated at elevated [CO2] may have lost their capacity to form effective symbiosis at ambient [CO2] and that was translated at whole plant level through metabolic impairment.